A Review On Polymeric Micellar Nanocarriers - DHEMBRE G.N; MOON R.S; KSHIRSAGAR R.V. (International Journal of Pharma and Bio Sciences, 2011)
Micelles, self-assembling nanosized (5–100 nm) colloidal particles with a hydrophobic core and hydrophilic shell are currently successfully used as pharmaceutical carriers for water-insoluble drugs and demonstrate a series of attractive properties as drug carriers. These polymeric miscellar nanocarriers have applications in drug delivery primarily such as anticancer therapy, to the brain to treat neurodegenerative diseases, antifungal agents, stimuli-responsive nanocarriers for drug and gene delivery, Ocular drug delivery. Targeted drugs will hopefully reduce adverse reactions by limiting their action to cancer tissue only.